The Role of Nitrogen-Efficient Cultivars in Sustainable Agriculture - Franz Weisler; Torsten Behrens; Walter J. Horst (The Scientific World Journal)
To improve nitrogen (N) efficiency in agriculture, integrated N management strategies that take into consideration improved fertilizer, soil, and crop management practices are necessary. This paper reports results of field experiments in which maize (Zea mays L.) and oilseed rape (Brassica napus L.) cultivars were compared with respect to their agronomic N efficiency (yield at a given N supply), N uptake efficiency (N accumulation at a given N supply), and N utilization efficiency (dry matter yield per unit N taken up by the plant). Under conditions of high N supply, significant differences among maize cultivars were found in shoot N uptake, soil nitrate depletion during the growing season, and the related losses of nitrate through leaching after the growing season. Experiments under conditions of reduced N supply indicated a considerable genotypic variation in reproductive yield formation of both maize and oilseed rape. High agronomic efficiency was achieved by a combination of high uptake and utilization efficiency (maize), or exclusively by high uptake efficiency (rape). N-efficient cultivars of both crops were characterized by maintenance of a relatively high N-uptake activity during the reproductive growth phase. In rape this trait was linked with leaf area and photosynthetic activity of leaves. We conclude that growing of N-efficient cultivars may serve as an important element of integrated nutrient management strategies in both low- and high-input agriculture.